The Effect of Breadfruit Leaf Extract (Artocarpus Altilis P) on Spatial Memory of in Male Strain Mice which Indicated by Alcohol - M. B. A. Kadir; E. R. Kasimo (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Spatial memory is working memory that is used to recall when performing certain tasks which is a combination of attention, concentration, and short-term memory. Breadfruit leaves contain compounds flavonoids, tannins, saponins that are as antioxidants that can prevent cognitive disease. Purpose: This study was to determine the effect of breadfruit leaf extract on spatial memory in 10% alcohol-induced mice using the Y-Maze Methods: Method: This study used 25 mice which were divided into 5 groups, namely the Biloba Gingko positive group, the Na-CMC Negative Group and the treatment group consisted of doses of 1 10, 15, 20 mg / 20 grams BB of Mice. Every 10% alcohol-induced mice was then tested by inducing preparations according to the treatment group. The results of the time calculation on Y maze are statistically analyzed with one-way ANOVA Results: From the results of the y maze test it is known that gingko biloba gives the best effect then the treatment group with a dose of 20 mg, the group 15 mg and 10 mg, and the negative group giving Na -CMC. Conclusion: The results of this study concluded that the breadfruit leaf extract (Artocarpus altilis P) can improve the spatial memory of alcohol-induced mice 10%.